Extracting the Topographic Features as a Pragmatic Survey for Landslide Susceptibility Analysis - Tutur Afdol Marifa; Arif Setio Wibowo; Dzaky Alfaiz Halza; Linda Permata (Jurnal Teknologi Sumberdaya Mineral, 2021)
Landslide susceptibility mapping in the mountainous area has become crucial for taking any precautions and imperative for any disaster management. As safety factor is currently widely used to indicate the ratio of strength to stress in a unit column, it lacks what matters to the disaster response unit – the probability in which a landslide can occur in a place. A value of safety factor shows whether a unit column will fail (SF >1) but does not lead to which unit column will be prioritized for monitoring and prevention measures. Therefore, unit slopes are generated based on the watersheds to part the study area. Before evaluating the landslide movement, and types, slope analyses is required. Several references of slope classification are chosen to gain the descriptive characteristics of a certain unit column and its correlation to other topography parameters. This research paper is a step before limit equilibrium analysis where the ratio of strength-to-stress calculation cannot disregard the slope behavior and soil thickness.